Accounting Recognition of Asset Abandonment and Site Restoration - Rena Maya Cahyanti; Aruna Wirjolukito (AFEBI Accounting Review, 2020)
This research will discuss the recognition of asset abandonment and site restoration or commonly known as ARO (Asset Retirement Obligation) in oil and gas company. The purpose is to be able to provide an overview that can be used by companies in calculating ARO that must be paid at the end of the contract period. The formulation of the problem is which method is used to determining the amount of asset abandonment and site restoration or ARO that is appropriate to overcome the potential problems that arise at the end of the contract period. This research is carried out by using a mixed method in analyzing the findings, so it will find the in-depth findings which will be useful to assist the company's management in making decisions. Signal theory is a theory that will be chosen in this research. This research will use three stages of analysis, such as descriptive analysis, content analysis, and constant comparative analysis. Based on the results it might found that the recognition of asset abandonment and site restoration carried out according to regulations apply. While company uses the method of calculating liabilities based on future values that is continually calculate in present value.   Keywords: Contingent liabilities, provisions, liability for asset abandonment and site restoration